Perlindungan Hukum bagi Pelaku Usaha dalam Kegiatan Bisnis Formal di Indonesia: Pendekatan Yuridis Normatif - Husnaini, Husnaini (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Legal protection for business actors is very important to create a fair, stable, and sustainable business environment within the framework of the rule of law. Formal businesses in Indonesia, whether run by corporations, cooperatives, or micro, small, and medium enterprises, are not affected by various legal risks that can hamper their operations. The purpose of this study is to examine how and how effectively legal protection is provided to business actors who run formal businesses in Indonesia, which are protected by applicable laws and regulations. The research method used is normative legal research using a legislative, conceptual, and comparative approach. Research materials include legislation in the field of business law, legal doctrine, and relevant scientific works. The results of the study show that Indonesia normatively has sufficient legal instruments to protect business actors, especially by regulating contracts, business competition, and intellectual property rights. However, various obstacles continue to hinder the implementation of such legal protection. Some of these obstacles include legal uncertainty, lack of law enforcement, and limitations on business actors' access to the judicial system. Therefore, regulatory harmonization, improved law enforcement efficiency, and institutional reform are needed to provide better and fairer legal protection for formal businesses in Indonesia.